Developing markets for agrobiodiversity: Securing livelihoods in dryland areas - Giuliani, A. (2007)
Reduced agrobiodiversity can leave communities highly vulnerable to changing climatic, economic and political pressures.This book, based on cutting edge research in Syria by Bioversity International (IPGRI), presents practical proposals for establishing markets and securing livelihoods in difficult dryland areas.One of a new series of Earthscan Research Editions – high level research monographs in a wide range of disciplines within sustainable development.Four crops - maize, potatoes, rice and wheat - provide more than 90 per cent of the world's food. Increasingly, old varieties of even these crops are disappearing as farmers and consumers strive for more uniformity in food products. This narrowing of the diversity of agricultural systems' main components has a knock-on effect on less obvious elements, such as insects that play a role in pollinating plants or controlling pests, and the soil organisms that help plants extract nutrients from the soil. Also, farmers need a broad base of agrobiodiversity to be able to respond and adapt to environmental changes and to improve their production. This is especially important in the face of climate change and changing economic and political pressures.This book from Bioversity International describes a study, conducted in Syria, of how communities are developing markets for local products derived from neglected and underutilized plants. Based on concrete case studies, the data and processes documented in the book show the potential of biodiversity to make a significant contribution to livelihood security in communities that inhabit difficult environments with unique resources. The study also highlights the importance of local cultural knowledge and institutions in sustainable development of biodiversity markets. Available on sale at £54.00 from Earthscan.co.uk